Preserve and Promote the Values Cultural Belief of the Khmer People in An Giang Province, Vietnam - Nguyen Chi Hai (CV. Literasi Indonesia, 2021)
Cultural belief is a unique feature that has an important value in the spiritual life of the Khmer people in An Giang province. It is a bold combination of indigenous and religious colors, most of the Khmer in An Giang believe in Buddhism, taking it as one of their ways of life, as solid spiritual support to adjust behavior, and handling interpersonal, interpersonal, and social relationships. Cultural beliefs have created for the Khmer in An Giang to have a rich, unique spiritual life, bringing their own identity, contributing to diversity in the culture of the country. The article aims to highlight the manifestations of cultural belief and point out the values of cultural belief in the spiritual life of Khmer people in An Giang province, offering some solutions to contribute to preserving, preserving the cultural belief of the Khmer people. Thereby, to preserve and promote cultural beliefs in the spiritual life of the Khmer people in An Giang province in the trend of international integration.